A strategy for dual biopolymer production of P(3HB) and γ‐PGA. Issue 7 (7th April 2017) - Sukan, Artun; Roy, Ipsita; Keshavarz, Tajalli
Abstract: BACKGROUND: Production of biopolymers has gained considerable attention because of their biodegradability, biocompatibility, and as suitable replacements for mineral‐based polymers. Despite advances in the production process, a notable drawback still exists due to high production cost. The aim of this work is to provide a production strategy for cost reduction. The suggested process may be adapted to other polymers, useable by a wide audience in biopolymer research. RESULTS: Dual production of two commercially important biopolymers, P(3HB) and γ‐PGA, in a single batch from cheap substrates was studied, as proof of concept, for feasible low cost dual biopolymer production. Dual production from a single batch yielded 1 g L −1 P(3HB) and 0.4 g L −1 γ‐PGA using Bacillus subtilis OK2 ( B. subtilis OK2). When orange peel was substituted as a cheap carbon source for dual production, coupled pH and dissolved oxygen control proved to be essential to overcome the inhibition imposed by the non‐sugar components of the substrate. Cell lysis and release of P(3HB) granules in the dual production medium can be exploited of as a new approach for separation of this polymer. CONCLUSION: This proof of concept study provides a new approach from upstream to downstream processing for low cost production of dual biopolymers. © 2017 Society of Chemical Industry